Proyeksi Kebutuhan Minyak Goreng di Kabupaten Kutai Kartanegara Tahun 2024 - Ali Akbar; Iskandar Iskandar; Erwinsyah Erwinsyah; Sundoyo Sundoyo; Martain Martain (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the cooking oil demand in Kutai Kartanegara Regency in 2024. The research uses secondary data published by the Central Bureau of Statistics (BPS). The data analysis tool used is the geometric projection method. The results of this study indicate that the demand for cooking oil in Kutai Kartanegara Regency in 2024 is projected to reach 7,271.2 tons. Kutai Kartanegara Regency has significant potential in palm oil production, with a total production in 2023 reaching 3,363,058.16 tons. By calculating the palm oil yield at 23%, Kutai Kartanegara Regency has the potential to produce its own cooking oil from the processing of local palm oil. The percentage of oil produced from palm oil production, after being converted into CPO, exceeds the demand for cooking oil produced (produced 773,503.38 tons, required 7,271.2 tons).